Plan Curricular y la Formación por Competencias en Estudiantes de Administración - UNMSM - Rivera León, Félix Armando (2020)
Our research seeks to establish a relationship between two variables, the Curriculum Plan and the Student Competency Training at the Professional School of Administration of the National University of San Marcos, this research was carried out during the years 2017-2018. The curricular plan is the north of all educational process in any university; On the other hand, the market requires that the students to graduate have sufficient competencies to face not only the labor market, but life itself. We consider the university as a school where students acquire the same competences that must be progressive as the modules progress through the cycle. The present investigation is typified as basic, primary, descriptive, correlational, quantitative, bivariate and transactional. The sample that was obtained is 80 students, using statistical software it was concluded that there is a moderate relationship between the curriculum plan and training by competencies.